Epidemiological and Clinical Characteristics of Patients with Pressure Ulcers in Butembo, Democratic Republic of the Congo - Moise Muhindo Valimungighe; Franck Katembo Sikakulya; Alexandre Amini Mitamo; Joël Kambale Ketha; Michel Kalongo Ilumbulumbu; Séverin Uwonda Akinja (Archives of Current Research International, 2018)
Background: Pressure Ulcers constitute a public health problem. The objective of this study was to determine the epidemiological and clinical characteristics of patients with pressure ulcers in Butembo. Methods: This was a descriptive cross-sectional study from September 2016 to February 2017, carried out at the Matanda hospital and Cliniques Universitaires du Graben in Butembo, Province of North-Kivu, Democratic Republic of the Congo. Results: Among 762 patients hospitalised in the surgery department of Matanda hospital and Cliniques Universitaires du Graben, 33 had pressure ulcers i.e. prevalence of 4.3%. Among them, there were 19 males and 14 females with mean age of 46.2 years. The mean time of appearance of pressure ulcers was 26.6 days; 75.8% of pressure ulcers were developed in hospital. 19 cases (57.6%) had second-degree pressure ulcers; sacral localisation was the most recorded in 51.5% or 17 cases. Nine patients out of 33 or 27.3% who had pressure ulcers had a traumatic neurological deficit as well as those with disabling medical conditions. Conclusion: Pressure ulcers remain a real public health problem in our community. They concern any patient, regardless of age or gender. Special attention should be paid to patients with conditions that lead to prolonged bed rest.